2021
DOI: 10.3390/toxins13120909
|View full text |Cite
|
Sign up to set email alerts
|

Indoxyl Sulfate Contributes to mTORC1-Induced Renal Fibrosis via The OAT/NADPH Oxidase/ROS Pathway

Abstract: Activation of mTORC1 (mechanistic target of rapamycin complex 1) in renal tissue has been reported in chronic kidney disease (CKD)-induced renal fibrosis. However, the molecular mechanisms responsible for activating mTORC1 in CKD pathology are not well understood. The purpose of this study was to identify the uremic toxin involved in mTORC1-induced renal fibrosis. Among the seven protein-bound uremic toxins, only indoxyl sulfate (IS) caused significant activation of mTORC1 in human kidney 2 cells (HK-2 cells).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 50 publications
2
21
0
1
Order By: Relevance
“…IS gets quickly excreted through the urine in healthy renal function; however, it accumulates in the blood 9 and causes renal dysfunction in various organs 39 . IS, when taken up by cells and tissues, promotes tissue fibrosis by increasing oxidative stress 40 and inflammation 41 . Additionally, IS polarizes macrophages into a proinflammatory phenotype (M1 macrophages), 42 which contributes to tissue damage 43 .…”
Section: Discussionmentioning
confidence: 99%
“…IS gets quickly excreted through the urine in healthy renal function; however, it accumulates in the blood 9 and causes renal dysfunction in various organs 39 . IS, when taken up by cells and tissues, promotes tissue fibrosis by increasing oxidative stress 40 and inflammation 41 . Additionally, IS polarizes macrophages into a proinflammatory phenotype (M1 macrophages), 42 which contributes to tissue damage 43 .…”
Section: Discussionmentioning
confidence: 99%
“…HK-2 cells are human-derived proximal tubular epithelial cells and have been commonly used as an in vitro model to evaluate drug nephrotoxicity and the potential mechanisms of renal diseases ( Qiu et al, 2018 ; Bejoy et al, 2022 ). The uremic toxins indoxyl sulphate and p-Cresyl sulphate are taken up into HK-2 cells via OATs and induce cytotoxicity in HK-2 cells, suggesting that OATs are expressed in HK-2 cells and contribute to the cytotoxicity of toxins ( Motojima et al, 2003 ; Miyamoto et al, 2011 ; Nakano et al, 2021 ). In the present study, protein expressions of both OAT1/3 and DHP-I were identified in HK-2 cells, which confirms that HK-2 cells are a suitable model for the investigation of DDIs mediated by OAT1/3 and DHP-I.…”
Section: Discussionmentioning
confidence: 99%
“…discovered that indoxyl sulphate (IS) contributes to mammalian target of rapamycin complex1 (mTORC1)‐induced RF via the organic anion transporters/nicotinamide adenine dinucleotide phosphate (NADPH) oxidase /ROS pathway. After IS enters cells, mTORC1 is activated by producing ROS associated with NADPH oxidase activation, which leads to EMT of renal tubular epithelial cells, differentiation of fibroblasts to myofibroblasts and inflammatory responses by macrophages 43 …”
Section: Relieving Oxidative Stressmentioning
confidence: 99%